2020
DOI: 10.3164/jcbn.19-98
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of hepatocellular carcinoma after hepatitis C virus eradication following direct-acting antiviral treatment: relationship with serum zinc

Abstract: The recently approved direct acting antivirals (DAA) agents are effective in terms of sustained virologic response (SVR) rates and are well tolerated in most hepatitis C virus (HCV) patients. This study aimed to analyze the association between serum zinc levels in patients who developed hepatocellular carcinoma (HCC) following HCV eradication after DAA treatment. The retrospective study included 769 HCV infected patients who achieved SVR after DAA treatment. We calculated the annual incidence rate of HCC and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 49 publications
(59 reference statements)
2
7
0
Order By: Relevance
“…The results of the present study demonstrated that the cumulative incidences of HCC were 1.4%, 3.2%, 4.9% and 6.8% at 2, 3, 4 and 5 years, respectively, from EOT with DAAs. Previous studies have reported that the 3‐year cumulative incidence of HCC in patients who received DAA treatment was 2.4%–6.6%, consistent with our study 28–30 …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The results of the present study demonstrated that the cumulative incidences of HCC were 1.4%, 3.2%, 4.9% and 6.8% at 2, 3, 4 and 5 years, respectively, from EOT with DAAs. Previous studies have reported that the 3‐year cumulative incidence of HCC in patients who received DAA treatment was 2.4%–6.6%, consistent with our study 28–30 …”
Section: Discussionsupporting
confidence: 92%
“…According to the ROC value for HCC occurrence of multiple parameters at EOT in 561 patients, the cut-off values for parameters were set and are shown in HCV eradication by DAAs. 14,[28][29][30][31][32][33][34][35][36][37][38] The results of the present study demonstrated that the cumulative incidences of HCC were 1.4%, 3.2%, 4.9% and 6.8% at 2, 3, 4 and 5 years, respectively, from EOT with DAAs. Previous studies have reported that the 3-year cumulative incidence of HCC in patients who received DAA treatment was 2.4%-6.6%, consistent with our study.…”
Section: Roc Analysis and Cut-off Valuessupporting
confidence: 51%
See 2 more Smart Citations
“…reported that, in patients who achieve HCV eradication after direct acting antiviral treatment, serum Zn concentrations before and at the end of antiviral treatment are a risk factor for developing HCC. 36 Miwa et have reported that Zn deficiency is likely to be a predictor of both the development of hepatic encephalopathy, and mortality in patients with liver cirrhosis and hepatic encephalopathy. 37 Imai et al…”
Section: Discussionmentioning
confidence: 99%